DECYZJONIZM ZAMIAST DEBATY? O PRZECIWSTAWNYCH WZORACH DZIAŁANIA W SFERZE PUBLICZNEJ - Pluciński, Przemysław (Wydział Prawa i Administracji UAM, 2011)
Artykuł podejmuje problem sporu między dwiema przeciwstawnymi teoriami demokracji i sfery publicznej: ujęciem agonistycznym (reprezentowanym przez klasyków Hannah Arendt oraz Carla Schmitta) oraz teorią deliberacyjną (w artykule ograniczoną do teorii działania komunikacyjnego Jürgena Habermasa). Autor rekonstruuje istotę sporu między Chantal Mouffe a Jürgena Habermasem, szczególny nacisk kładąc na krytykę liberalizmu Chantal Mouffe, wydobytą z myśli Carla Schmitta. Polemika ze stanowiskiem Mouffe dotyczy przede wszystkim wizji pluralizmu, jaki oferują perspektywy agonistyczna i komunikacyjna. Kryterium różnicujące stanowi tu kwestia inkluzyjności/ekskluzyjności prezentowanych wizji sfery publicznej w perspektywie przedmiotowej (o co toczy się spór?) oraz podmiotowej (kto uczestniczy?/kto jest wyłączany?). Konkluzja jest następująca: to krytykowana za liberalne uwikłanie perspektywa dyskursywna oferuje więcej przestrzeni dla demokratycznego pluralizmu.

The paper deals with the controversy between two antithetical theories of democracy and the public sphere: the agonistic approach (represented by the classics: Hannah Arendt and Carl Schmitt) and the deliberative theory (in this paper reduced to Jürgen Habermas’ communicative theory). The author offers a reconstruction of the essence of the controversy between Chantal Mouffe and Jürgen Habermas, focusing on Mouffe’s critique of liberalism derived from Carl Schmitt’s thought. The paper ventures to challenge Mouffe’s approach, particularly the view of pluralism offered by both, the agonistic and the communicative perspectives. What makes the two perspectives distinct is the issue of inclusiveness exclusiveness of the object (what is the conflict about?) and the subject (who participates and who is excluded?). The paper concludes with a statement that it is the discursive communicative approach (criticised for its liberal roots) that offers much more space for democratic pluralism.
DECISIONISM INSTEAD OF A DEBATE? ON THE ANTITHETICAL PATTERNS OF ACTION IN THE PUBLIC SPHERE
Keywords: sfera publiczna; public sphere; agonizm; agonism; teoria działania komunikacyjnego; The theory of communicative action; Racjonalność; Rationality; Pluralizm; Pluralism